Rainfall-Induced Slope Stability on Soil-Rock Mixture - Adefi Abioga; Arief Rachmansyah; Yulvi Zaika (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Many landslides are caused by rainfall, and antecedent rainfall plays a major role in slope failure. The landslide in Bululawang, Blitar, is one example of a slope that failed during a rainfall event. The stratification of the rock and soil in this area is complicated. There are several blocks of rock and clay-based soil in the landslide region, along with limestone. This study aims to examine how rainfall affects rock-mixed soil. Electrical resistivity tomography (ERT) was conducted to model the slope stratification combined with boring to verify the results. Soil properties mixed with rock (SRM) were estimated by rock block proportion on the slope. A transient model of slope stability analysis was created using the SEEP/W program to simulate slope seepage and SLOPE/W to compute slope stability. Following the antecedent precipitation, an extreme rainfall event occurred. The findings demonstrate how the slope in Bululawang Blitar is affected by antecedent rainfall, affecting the slope's initial state before applying intense rainfall. The elevation of the groundwater level and the pore water pressure on the slope are altered by antecedent rainfall. When examined, this phenomenon will impact the slope's safety factor. The slope safety factor (FoS) was reduced by 31.48% from 1.542 to 1.057 in the event of extreme rainfall, which does not satisfy the requirement for a slope safety factor of 1.25. The slope design utilizing a counterweight can optimally elevate the slope safety factor (FoS) from 1.057 to 1.461, which exceeds the required value of 1.25. SRM-type soil possesses high permeability, resulting in a rapid decline in the stability value of the slope in the event of extreme rainfall. Consequently, an early warning system tool is necessary to alert against landslide hazards.